Women Inheritance Right: Gender Relationship According to Tafsir al-Mishbah - Nurdalia Bate (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
This study discusses women’s inheritance rights; gender relations, according to Tafsir Al-Mishbah. It was library research. The problems were; 1) How did Muslim intellectuals view women’s inheritance rights in terms of their role and position in the family? 2) What was M. Quraish Shihab’s view of it in Tafsir Al-Mishbah? It was discussed with a normative, sociological, philosophical-theological, and historical approach. While the method used was descriptive-analytical and comparative. It was found that Muslim intellectuals had the view that the division of inheritance that had been stipulated in the Qur’an was not a final decision. It applied and was in sync with the conditions at the time of the verse revelation, in a patrilineal system. Now, it needs to be reviewed because the Qur’an requires justice. Meanwhile, M. Quraish Shihab views a final determination, based on Q.S. an-Nisa verse 11, which meant: “This is a decree from Allah. Verily, Allah is All-Knowing, All-Wise.” The God argued that inheritance cannot be covered by ijtihad. Yet, there was a solution offered by distributing the property while people were still in good health.